Pengaruh Kompetensi dan Kepuasan Guru Terhadap Kinerja Guru SMA Negeri di Wilayah Bakorwil I Jawa Timur - Moh Arifin (Universitas 17 Agustus 1945 Surabaya, 2017)
This research talks about the Influence of Competence and Master's SatisfactionPerformance of High School Teachers in Bakorwil I Region of East Java. The populationof research is 1012 high school teachers. By using the Slovin formula with a tolerance of5%, the sample size was 287 respondents. Test model with Least Square Estimate estimation (GLS), structural equation model(SEM) analysis, proportional random sampling method and Amos 22 software, on 287respondents. The test results show the model (fit) seen from the GFI, AGFI, TLI, CFI,RMSEA and CMIN / DF values, respectively 0.942, 0.913, 0.964, 0.981, 0.064 and 1.588are all within the expected value range. The model is acceptable. The results showed that: 1). Teacher competence has a significant effect on teacher'ssatisfaction. 2). Teacher competence has a significant effect on teacher performance. 3).Teacher satisfaction has a significant effect on teacher performance.4). Teachercompetence has an indirectly significant influence on teacher performance throughteacher's satisfaction. Keywords: teacher competence, satisfaction, teacher performance